Evaluating and Differentiating Ankle Instability - Gribble, Phillip A. (J Athl Train, 2019)
Given the prevalence of lateral ankle sprains during physical activity and the high rate of reinjury and chronic ankle instability, clinicians should be cognizant of the need to expand the evaluation of ankle instability beyond the acute time point. Physical assessments of the injured ankle should be similar, regardless of whether this is the initial lateral ankle sprain or the patient has experienced multiple sprains. To this point, a thorough injury history of the affected ankle provides important information during the clinical examination. The physical examination should assess the talocrural and subtalar joints, and clinicians should be aware of efficacious diagnostic tools that provide information about the status of injured structures. As patients progress into the subacute and return-to-activity phases after injury, comprehensive assessments of lateral ankle-complex instability will identify any disease and patient-oriented outcome deficits that resemble chronic ankle instability, which should be addressed with appropriate interventions to minimize the risk of developing long-term, recurrent ankle instability.